Spectral transmittance of some ophtalmic lences in Malaysia - Sharanjeet-Kaur; M. Normazila; A.E. Ariffin (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2002)
This study was conducted to determine the spectral transmittance of some commonly dispensed ophthalmic lenses in Malaysia. The efficiency of these lenses in providing ocular protection against ultraviolet radiation was also examined. Eight lenses that are currently marketed in Malaysia as lenses with “UV-coating” were randomly selected for the testing. These lenses (Hoya, Essilor Orma, Optron, Sola, Igel, Zeiss, Vista Optics and American Optical) were obtained from a few optometric practices in Kuala Lumpur. They were marketed as lenses with "UV blocking" properties by virtue of the UV coat on them. A Spectrophotometer (Shimadzu UV-160A) was used to determine the spectral transmittance of these lenses. It was found that Hoya, Essilor, Optron, Sola and Igel lenses provided good protection against ultraviolet B radiation. However, there was transmission (10 to 15%) of ultraviolet C radiation. It was also found that these lenses transmitted some ultraviolet A radiation, averaging at about 28% for all 5 lenses. Zeiss, Vista Optics and American Optical lenses were all found to be capable of blocking ultraviolet C radiation. However, Zeiss lens transmitted some ultraviolet A and Vista Optics lens transmitted some ultraviolet A and B radiations as well. The American Optical lens was the only lens that blocked the transmission of all of ultraviolet radiations A, B and C. This study shows that UV-coated American Optical lenses as marketed in Malaysia provide sufficient protection against ultraviolet radiation.